2009
DOI: 10.1159/000230011
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Instability: Current Pathophysiological Concept

Abstract: The role of urethral pressure variations during filling cystometry is seldom assessed as a potential cause of voiding dysfunction and/or storage disorders. In this article, we review current research in the field of urethral pressure variations and discuss the way of determining urethral pressure variations, its value for the clinical practice and hypothesize the origin of urethral pressure variations. The observation and recognition of urethral pressure variations (urethral instability) could be valuable in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Six papers were excluded because of mixed gender studies . Six expert opinion reviews were excluded . When multiple papers were published on the basis of a single patient cohort, only one paper of those, with the largest cohort, was included, others were considered duplicate and excluded .…”
Section: Resultsmentioning
confidence: 99%
“…Six papers were excluded because of mixed gender studies . Six expert opinion reviews were excluded . When multiple papers were published on the basis of a single patient cohort, only one paper of those, with the largest cohort, was included, others were considered duplicate and excluded .…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that one and the same pathophysiological mechanism participates in female stress, urge, and mixed incontinence (17). Moreover in 2009, Groenendijk et al stated that it makes sense to measure and register detrusor and urethral function during filling and voiding (18). Despite the fact that most authors consider urethral pressure variations, exceeding an amplitude of 15cmH 2 O, as an abnormal finding (6-12) the significance of these fluctuations is still unclear, and the terms ‘urethral instability’ or ‘unstable urethra’ lack clarity and are not accurately defined by the ICS today.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that neuronal nitric oxide (NO) synthase, known for its significant role in nociceptive pathways in the bladder has also been found in human female striated urethra sphincter (20). It may be that contraction of the detrusor is caused by a fall in urethral pressure (18). However, looking at the traces, it is very difficult to determine (Figure-1) which came first: detrusor overactivity, then urethral pressure drop or vice versa, or both appeared at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of urethral pressure variations during filling cystometry (urethral instability) has been well documented by various investigators, and said to be responsible for the sensation of urgency and for incontinence. 42 Mechanical stimulation of the urethra, especially the flow of urine, may facilitate the micturition reflex as mentioned above, and reflexes between the urethra and bladder play an integral role in the neural control of the lower urinary tract. 25 Studies in animals have demonstrated the basis for an excitatory urethra-to-bladder reflex, showing that sensory nerves in the wall of the urethra fire in response to urethral urine flow and electrical stimulation, and that this activity initiates bladder contractions in the quiescent bladder and augments ongoing contractions in the active bladder.…”
Section: The Proximal Urethral Mucosa As a Possible Initiator Of Overmentioning
confidence: 99%